2015
DOI: 10.1515/msd-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Aroma Compounds on Senzorial Traits of Wines From the Apold Depression

Abstract: ABSTRACT:The present study aims at investigating aroma compounds in three wine varietals (Pinot gris, Traminer roz, Riesling) from Apold, the county of Sibiu, production of 2014, and their importance in realizing the sensorial profile of wines. Thus, it is ascertained that Traminer roz contains the highest amount of esters -583.846 mg/L, a value that leads to the sensorial identification of floral and fruity notes. Higher alcohols determined through chromatography imprint specific traits to Pinot gris wines: b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Aldehydes are mainly formed during wine aging, and they contribute to the sour, almond and vanilla aroma notes [56]. Benzaldehyde gives the almond aroma note, but it was detected in the concentration 0.08-0.11 mg/L, which is below the OTL.…”
Section: Discussionmentioning
confidence: 92%
“…Aldehydes are mainly formed during wine aging, and they contribute to the sour, almond and vanilla aroma notes [56]. Benzaldehyde gives the almond aroma note, but it was detected in the concentration 0.08-0.11 mg/L, which is below the OTL.…”
Section: Discussionmentioning
confidence: 92%
“…In terms of the sensory attributes, the analyzed Argentinian wine samples were characterized by “green” color, “woody” aroma, and “warmness”, and showed anti-correlation with the OQJ while the wines from New Zealand (Gisborne) were strongly correlated with the OQJ, and were characterized by attributes, such as “floral” aroma, “stone-fruit” flavor, “yellow” color, “caramelized” aroma, and “tropical fruit” aroma. The volatile compounds that characterized the analyzed wines from New Zealand (Gisborne) were III: isobutyl alcohol, responsible for alcohol, pungent, solvent, or bitter aromas [ 29 ], XXVII: benzenebutanal, XXV: ethyl phenylacetate, esters responsible for fruit, sweet odors [ 30 ], and XXVI: phenethyl acetate, known for the contribution of fruity notes in wine [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results from this study showed that in Pinot Gris wines, for the “floral “aroma, the volatile compounds isobutyl alcohol, linalool, ethyl phenylacetate, and decanoic acid showed a positive effect. Indeed, previous studies have shown that volatile compounds, such as hexanoic acid, octanoic acid, linalool, and decanoic acid (volatile fatty acids), were identified in Pinot Gris wines, which were responsible for imparting a floral aroma [ 29 , 53 ]. For Pinot Noir, volatile compounds, such as isopentanol, 1-hexanol, benzaldehyde, ethyl phenylacetate, and ethyl isopentyl succinate, showed a positive influence on the “green bell pepper” aroma.…”
Section: Discussionmentioning
confidence: 99%
“…Thies include flavonols, hydroxylbenzoic acids, flavanols and hydroxycinnamic acids. The bitterness and the astrigency af red wine is a result of flavanols and phenolic acids, and the color is insured of the quantity and quality of monomeric anthocyanins ( Lengyel et al 2015, He et al, 2012b.…”
Section: Introductionmentioning
confidence: 99%